2022
DOI: 10.3389/fpsyg.2022.1006184
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Chinese preschool principal leadership styles and teacher leadership: Exploring the mediating effect of psychological capital

Abstract: Enhancing teacher leadership is not only one of the approaches to improving teaching and learning, but it is also essential to the success of education reform. Based on leader-member exchange theory, 294 preschool teachers in China were surveyed, and a structural equation model was established to explore the relationship between the participating teachers' principal leadership style, teacher leadership and psychological capital. The findings revealed a significant positive correlation between transformational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
2
0
1
Order By: Relevance
“…Perceptions of what constitutes an effective leadership style for a given educational institute must consider the situation's specific goals and challenges [54]. A distributed leadership style, for example, may be more appropriate if the goal is to empower employees and promote innovation, whereas a transformational leadership style may be more appropriate if the goal is to make a significant change or overcome a challenge [53][54][55]. The results of the present work revealed that academics have positive perceptions of distributed leadership styles.…”
Section: Discussionmentioning
confidence: 74%
“…Perceptions of what constitutes an effective leadership style for a given educational institute must consider the situation's specific goals and challenges [54]. A distributed leadership style, for example, may be more appropriate if the goal is to empower employees and promote innovation, whereas a transformational leadership style may be more appropriate if the goal is to make a significant change or overcome a challenge [53][54][55]. The results of the present work revealed that academics have positive perceptions of distributed leadership styles.…”
Section: Discussionmentioning
confidence: 74%
“…A nivel mundial el mundo fue impactado por la propagación del COVID-19 en donde ha dejado o ha generado fuerte pérdidas económicas, sociales y aún más afectando el aspecto emocional de las personas en especial los infantes y las personas adultas quienes se convirtieron en personas vulnerables, en este caso las consecuencias o la forma de vivir después de la pandemia, los grandes cambios que se ha generado en campo educativo y aún más en los actores educativos, los estudiantes, padres de familia y la comunidad en general (Zhang et al, 2022).…”
Section: Introductionunclassified
“…Enhancing teachers' leadership style not only enhances teaching effectiveness but also it brings reforms in education. According to leader-member exchange theory (LMX) encouraging universities teachers, instructors and spirituality and implement ethical and responsible practices could help higher educational institutions to bring educational reforms and enhance teachers' effectiveness (Zhang, Wu, Liu, Ren & Lin, 2022). Numerous studies have been conducted on leadership, followership but to the best of researcher's knowledge limited empirical evidence is available on effect of spirituality on servant leadership to enhance leadership effectiveness (Busari, 2011;Sendjaya, Sarros & Santora, 2008).…”
Section: Introductionmentioning
confidence: 99%